2020
DOI: 10.1371/journal.pntd.0008200
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and epidemiological analysis of a Burkholderia cepacia sepsis outbreak from a tertiary care hospital in Bangladesh

Abstract: Background Burkholderia cepacia complex (Bcc) is a group of serious pathogens in cystic fibrosis patients and causes life threatening infections in immunocompromised patients. Species within the Bcc are widely distributed within the environment, can survive in the presence of disinfectants and antiseptics, and are inherently multidrug resistant (MDR). Methods Dhaka Medical College Hospital (DMCH) patients with a B. cepacia positive blood culture between 20 October 2016 to 23 rd September 2017 were considered a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 27 publications
1
2
0
5
Order By: Relevance
“…17 Another study in Bangladesh showed 100% sensitivity to Meropenem, and 93% of isolates were resistant or intermediate to levofloxacin. 19 The results from SENTRY Antimicrobial surveillance program showed greater than 90% susceptibility to Minocycline, similar to our results in which Minocycline is considered the most effective antibiotic. 20 However, the current clinical information is not adequate, and further studies are necessary to determine the in vitro efficacy of these antimicrobial agents for Burkholderia cepacia infections.…”
Section: B Cepacia Was Isolated From Clinical Samples Of 419supporting
confidence: 90%
“…17 Another study in Bangladesh showed 100% sensitivity to Meropenem, and 93% of isolates were resistant or intermediate to levofloxacin. 19 The results from SENTRY Antimicrobial surveillance program showed greater than 90% susceptibility to Minocycline, similar to our results in which Minocycline is considered the most effective antibiotic. 20 However, the current clinical information is not adequate, and further studies are necessary to determine the in vitro efficacy of these antimicrobial agents for Burkholderia cepacia infections.…”
Section: B Cepacia Was Isolated From Clinical Samples Of 419supporting
confidence: 90%
“…(19) Mikroorganisme ini menyebabkan tiga masalah penting pada kelompok penderita CF, yaitu multi resisten terhadap agen antimikrobia, transmisi antar manusia (secara nosokomial ataupun nonnosokomial) serta menyebabkan sindrom cepacia. (20,21) Sindrom cepacia merupakan pneumonia yang sering diasosiasikan dengan septikemia. (21) Genus Burkholderia terdiri lebih dari 60 spesies.…”
Section: Burkholderia Cepacia (B Cepacia)unclassified
“…Kemampuan resistensi antibiotik ini terbukti dengan ditemukannya enzim betalactamase, efflux systems pada bakteri ini serta kemampuan bakteri ini hidup di lingkungan intraselular. (20,32) Bcc termasuk dalam kelompok bakteri Multi Drug Resistance (MDR). Berbagai mekanisme reesistensi pada Bcc diantaranya adalah inaktifasi enzimatik, pengubahan target obat, impermeabilitas dinding sel dan efflux pump.…”
Section: Biofilmunclassified
See 1 more Smart Citation
“…In 2002, Genomover III, which contains some of the more infectious strains of B. cenocepacia was reassigned to the species designation (8) . This bacterium was relatively unknown as a human pathogen until the mid-1980s, when it surfaced as a nosocomial infection at cystic fibrosis clinics (9) . Like many opportunistic pathogens, B. cepacia can establish an infection in any favorable environment.…”
Section: Introductionmentioning
confidence: 99%